(untitled) (BIRDEM Medical Journal, 2019)
Dengue is endemic in Bangladesh and is an emerging infection in many parts of the world. Its clinical manifestations are wide spectrum, may present as mild fever to shock. Muscle hematomas are rare complications in dengue hemorrhagic fever. We report a case of 21-year-old male with dengue hemorrhagic fever who developed right sided iliacus muscle hematoma. He presented with fever, progressive thrombocytopenia and evidence of plasma leakage. During the recovery phase, he developed severe pain in right hip during movement. Diagnosis was confirmed by pelvic computed-tomography scan and he was managed conservatively. Birdem Med J 2020; 10(1): 76-77